Chlorophyll a fluorescence as a tool to monitor physiological status in the leaves of Artemisia ordosica under root cutting conditions - Liu, Ying; Gong, Chuangang; Pei, Weihao; Fan, Kaixuan; Shen, Wenjing (Frontiers in Plant Science, 2024)
Background Root cutting caused by underground coal mining subsidence is among the leading causes of plant damage in western China. Detection of root cutting stress is of great importance in evaluating the degree of plant damage and changes in physiological conditions in underground coal mining disturbance conditions.The present study assessed the use of chlorophyll fluorescence OJIP transient data to evaluate the disturbance characteristics of root cutting stress on leaf photosynthetic mechanisms in the typical shrub Artemisia ordosica Krasch. Different root cutting ratios (10%, 20%, 30%, 50%, 75%, and 100%) were established on the roots of A. ordosica in the field, and the OJIP transient and JIP parameters of the leaves were measured.The overall OJIP curves and each OJIP step in leaves decreased as the root cutting ratio increased, but the impact was relatively small for root cutting ratios of less than 30%. Through the analysis of JIP parameters and the established energy pipeline model, it was found that the energy capture efficiency and electron transfer efficiency of photosystem II decreased as the root cutting ratio increased. Therefore, we also inferred that the threshold for the plant root cutting ratio at which leaf photosynthetic mechanisms begin to change is 30-50%.These results indicate that OJIP transient analysis can serve as a non-destructive, rapid technique for detecting plant root cutting stress in coal mining subsidence areas, which is of great value for non-destructive monitoring of plant root damage.